Luminescent DNA- and Agar-Based Membranes - Leones, R.
Luminescent materials containing europium ions are investigated for different optical applications. They can be obtained using bio-macromolecules, which are promising alternatives to synthetic polymers based on the decreasing oil resources. This paper describes studies of the DNA- and Agar-europium trif late luminescent membranes and its potential technological applications are expanded to electroluminescent devices. Polarized optical microscopy demonstrated that the samples are birefringent with submicrometer anisotropy. The X-ray diffraction analysis revealed predominantly amorphous nature of the samples and the atomic force microscopy images showed a roughness of the membranes of 409.0 and 136.1 nm for the samples of DNA(10)Eu and Agar(1.11)Eu, respectively. The electron paramagnetic resonance spectra of the DNA(n)Eu membranes with the principal lines at g approximate to 2.0 and g approximate to 4.8 confirmed uniform distribution of rare earth ions in a disordered matrix. Moreover, these strong and narrow resonance lines for the samples of DNA(n)Eu when compared to the Agar(n)Eu suggested a presence of paramagnetic radicals arising from the DNA matrix. The emission spectra suggested that the Eu3+ ions occupy a single local environment in both matrices and the excitation spectra monitored around the Eu emission lines pointed out that the Eu3+ ions in the Agar host were mainly excited via the broad band component rather than by direct intra-4f(6) excitation, whereas the opposite case occurred for the DNA-based sample.